2014
DOI: 10.1051/0004-6361/201322044
|View full text |Cite
|
Sign up to set email alerts
|

ChandraX-ray spectroscopy of a clear dip in GX 13+1

Abstract: Context. The source GX 13+1 is a persistent, bright Galactic X-ray binary hosting an accreting neutron star. It shows highly ionized absorption features, with a blueshift of ∼400 km s −1 and an outflow-mass rate similar to the accretion rate. Many other X-ray sources exhibit warm absorption features, and they all show periodic dipping behavior at the same time. Recently, a dipping periodicity has also been determined for GX 13+1 using long-term X-ray folded light-curves, leading to a clear identification of on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 64 publications
11
32
0
Order By: Relevance
“…This result is consistent with that found for other accreting NSs and also for XMM-Newton and Chandra spectra of GX 13+1 (e.g. Díaz Trigo et al 2012;D'Aì et al 2014 and reference therein). The soft component provides an inner temperature consistent with ∼ 0.6 keV for the two corrections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with that found for other accreting NSs and also for XMM-Newton and Chandra spectra of GX 13+1 (e.g. Díaz Trigo et al 2012;D'Aì et al 2014 and reference therein). The soft component provides an inner temperature consistent with ∼ 0.6 keV for the two corrections.…”
Section: Discussionsupporting
confidence: 92%
“…It also results more opaque, and probably cloudy, close to the plane of the disc. In addition, the absorption lines associated to the warm absorber are produced by highly ionised species and indicate bulk outflow velocities of ∼ 400 km s −1 (Ueda et al 2004;Madej et al 2013;D'Aì et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In the case of the observation with obsid 11814, a second XABS model is introduced in order to fit the non-outflowing ionized gas along the line of sight. The column density of GX 13+1 is in agreement with values found by Pintore et al (2014) andD'Aì et al (2014).…”
Section: Discussionsupporting
confidence: 89%
“…They showed that the RDPHA calibration provides more consis-tent centroid line energies and more physical fit parameters (such as the emission Gaussian line centroid energy and source inclination parameters obtained through the diskline model best fit). Using this correction, they found the energy of the iron mission line at 6.6 keV, and stated that it was consistent with the energies found by Díaz Trigo et al (2012) andD'Aì et al (2014). In the RDPHA correction, the energy scale is calibrated by fitting the peaks in derivative PHA spectra corresponding to the Si (∼1.7 keV) and Au (∼ 2.3keV) edges of the instrumental responses, where the gradient of the effective area is largest (XMM-SOC-CAL-TN-0306).…”
Section: Data Reductionsupporting
confidence: 78%